Representasi Konsep Diri Remaja Perempuan Pembaca Buku “Sebuah Seni Untuk Bersikap Bodo Amat” dari Mark Manson - Canesya Adzani; Gregorius Genep Sukendro (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2020)
Adolescence is a time of self-identification and self-development. The view of oneself that had developed in childhood strengthened in adolescence. This is in line with increasing age and life experience based on the facts experienced. All that makes teenagers can judge themselves good, and also vice versa, less good. Teenagers tend to look at the social media profiles of other teenagers and make comparisons with themselves. This comparison will unconsciously form an ideal self-concept whose standards are getting higher and further away from the self-concept possessed by adolescents today. Teenagers who get negative feedback from social media will find it difficult to accept themselves. There is always an assumption that other people around him will look negatively towards him. The question in this study is